臺灣主要港口附近海域混合波浪統計特性及推算模式建置研究(4/4) - 張憲國 (My University, 2016)
港灣工程規劃設計之設計波浪須由長期實測波浪資料來決定。近年來為解決現有記錄時間不足已發展類神經颱風波浪推算模式，但此技術仍需往昔的實測資料，但在環境有改變的情況下這些技術的可靠性仍需再評估。為提升國內波浪推算技術之正確性本研究針對臺中港以類神經模式與M5模式樹建立模式，再對兩者的適用性進行評估。 本研究以二維風浪數值模式模擬各場颱風對各港口造成的波場以供設計波浪的推算。另為響應國際航海學會(PIANC)對氣候變遷造成海事工程之影響議題，本研究對颱風與波浪資料利用多種趨勢檢測分析，在同時考慮季節性的變化與資料缺漏的狀況，估算資料趨勢以評估氣候變遷影響的顯著性，並將結果應用於設計波高的決定標準。

Design waves for marine structures are commonly determined by extreme analysis on long-term annual maximum wave data. However insufficient data are available for extreme analysis. The problem of insufficient data samples was solved by supplementation of simulated waves which were calculated by ANN wave simulation model developed by the Harbor and Marine Technology Center of Taiwan (IHMT). The accuracy of these wave data samples for extreme analysis should be promoted considering alternative approach and the effect on wave climate by recent global climate change. This project aims to not only establish the Ann wave simulation model for the Taichung harbor, but also to develop a new M5 wave model. Comparison on the simulated result by ANN and M5 models with observed data will show the prediction accuracy and applicability of both wave models. A numerical wave model of MIKE 21 SW will be used to calculate waves at Taichung harbors for chosen typhoons. The best predictions on wave among ANN, M5 and numerical wave models will be determined by comparing the simulated waves with observed data. Design waves for each harbor will be determined from most accurate wave samples. Responding to the issue of the impact of climate change on marine works proposed by World Association for Waterborne Transport Infrastructure (PIANC), several methods of trend detection is used to determine the trend of long-term observed typhoon’s waves of IHMT. Considering the climate change, applicable standard procedure for design wave was suggested by this research.
Hybrid wave calculation using modular model and numerical simulation for main harbors of Taiwan (4/4)
Keywords: 氣候變遷; 設計波; 二維數值模式; 臺灣主要港口; 風浪推算